2022
DOI: 10.1111/eea.13229
|View full text |Cite
|
Sign up to set email alerts
|

Host preference of the tree‐killing bark beetle Polygraphus proximus across a geographic boundary separating host species

Abstract: Ecologists and evolutionary biologists are broadly interested in how interactions between plants and insects vary among and across geographic ranges. When populations are geographically isolated (i.e., allopatric) by physical barriers, such as mountain ranges, straits, or waterways, geographic variation in traits among populations may be observed (Thompson, 1994). In response to natural selection, species-specific traits may provide a fitness advantage to a given population located in a particular area and not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 51 publications
2
9
2
Order By: Relevance
“…However, no positive correlation between host taxonomic proximity and host preference in P. proximus was observed in a previous study (Takagi, 2022). In contrast, this study showed that the relationship between taxonomic proximity and colonization success is complex.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…However, no positive correlation between host taxonomic proximity and host preference in P. proximus was observed in a previous study (Takagi, 2022). In contrast, this study showed that the relationship between taxonomic proximity and colonization success is complex.…”
Section: Discussioncontrasting
confidence: 98%
“…The results showed that the order of colonization success among the Abies species was not significantly different on either side of the Tsugaru Strait. These findings are consistent with those ofTakagi (2022) reporting that the Tsugaru Strait does not represent a geographic boundary of host preferences for P. proximus, indicating that host specialization has not occurred across the Tsugaru Strait.According to the PPH and a positive correlation between host preference and successful colonization (i.e., the preferencecolonization hypothesis) in bark beetles, the rates of successful colonization among the Abies species would be reflected by their host preference. Specifically, A. veitchii and A. firma were expected to exhibit the highest successful colonization rates, followed by A. homolepis and A. sachalinensis exhibiting the lowest rate.…”
supporting
confidence: 91%
See 3 more Smart Citations